Level of uncertainty in parents during the hospitalization of the newborn in a public hospital in Chiclayo, 2020 - Cordova Rodas, Natalie Lizeth (2021)
Objective: To determine the level of uncertainty in the parents during the hospitalization of the newborn in a public hospital in Chiclayo, 2020. Method: Quantitative research carried out through a pilot, descriptive, non-experimental and cross-sectional study; The population and sample consisted of 30 parents of hospitalized infants, the sampling was non-probabilistic for convenience. The scale uncertainty in the face of the disease - father / son form was used as an instrument. The reliability of the instrument was calculated in the SPSS version 25 software and a descriptive analysis was also performed according to the ordinal variable and its dimensions in the Excel 2016 statistical program. Results: During the newborn's hospitalization, 50% of the parents presented a high level of uncertainty, 36.67% regular and only 13.33% low level. In addition, the parents expressed agreement with the items: My son's treatment is very difficult to understand (53.33%), the course of my son's illness is constantly changing; they have good days and bad days (46.67%), I have many unanswered questions (43.33%), I can count on nurses when I need them (43.33%); doctors and nurses use colloquial language so that you can understand what they are saying (43.33%). General conclusion: 50% of the parents presented high levels of uncertainty regarding the hospitalization of the neonate due to their health status, treatment, diagnosis and prognosis, which can be ambiguous, complex, of which they have little information and prediction. Keywords: Uncertainty (D035501), parents (D010290), hospitalization (D006760), neonate (D007231)